Terminologies Related to Aruchi: A Literary Review - Kumari, Abhilasha; Mahant, Vividha; Chauhan, Meenakshi; Bala, Madhu; Devi, Riyanka (International Research Journal of Ayurveda & Yoga, 2024)
In Ayurveda, all diseases are manifested by Mandagni and also due to forceful expulsion and voluntary suppression of natural urges. Due to Mandagni digestion of food doesn’t occur properly so Rasadi Dhatu can’t be produced and this leads to many symptoms, such as Vishtambha, Sadana, Shirso Ruk, Murchha, Arochaka, and Avipaka. Charaka Samhita has explained the importance of Anna as it is the life of living beings and the whole world runs towards it. Only the digested food nourishes the Dhatu, Oja provides strength and complexion to the body. Furthermore, the suppression of Udgara, Kshudha, Kasa, and Ashru lead to Aruchi and many other diseases. In Ayurveda classical texts, there are various terminologies related to Aruchi such as Kshunasha, Bhaktadwesha, Annadwita, Annarasakheda, Annanabhinandana, Abhakhtachhanda, Annanabhilasha etc. This article presents the importance of these terms and how they are seemingly alike but different from each other.